The diversification of termites: Inferences from a complete species‐level phylogeny - Marcio R. Pie; Tiago F. Carrijo; Fernanda S. Caron (Zoologica Scripta, 2021)
Termites play a major role in a variety of ecological processes in tropical and subtropical biomes worldwide, such as decomposition, soil formation and aeration, and nutrient cycling. These important ecosystem services were achieved through their highly complex societies and remarkable adaptations, including the evolution of reproductive division of labour, the acquisition of endosymbionts and the capacity for extensive environmental engineering, yet the causes and consequences of their ecological success are still poorly understood. The goals of our study were (a) to provide the first complete, species‐level phylogeny of all currently recognized termite species by integrating the available genetic and taxonomic data, as well as methods of phylogenetic imputation and divergence time estimation; and (b) to explore variation in speciation rates among termite lineages. We provide the inferred relationships as a set of 1,000 pseudo‐posterior trees, which can be used in future comparative analyses. We demonstrate that speciation rates have been relatively constant throughout the history of termites, with two positive shifts in speciation rates: one at their origin of Euisoptera and the other concordant with evolution of Termitidae. On the other hand, there was no obvious trend towards deceleration in speciation rates for termites as a whole, nor within the most species‐rich families. The provided trees might represent a valuable resource for termite comparative studies by summarizing the available phylogenetic information, while accounting for uncertainty in the inferred topologies.